Antiretroviral Drug Resistance Surveillance among Treatment-Naive Human Immunodeficiency Virus Type 1-Infected Individuals in Angola - Bartolo, Ines (2015)
The prevalence of transmitted human immunodeficiency virus type 1 drug resistance in Angola in 2001 in 196 untreated patients was investigated. All subtypes were detected, along with unclassifiable and complex recombinant strains. Numerous new polymorphis. - Fundacao GlaxoSmithKline das Ciencias da Saude and Fundacao para a Ciencia e Tecnologia, Portugal [PTDC/SAU-FCF/67673/2006]; Fundacao para a Ciencia e Tecnologia, Portugal. - This work was supported by grants from Fundacao GlaxoSmithKline das Ciencias da Saude and Fundacao para a Ciencia e Tecnologia, Portugal (PTDC/SAU-FCF/67673/2006). Ines Bartolo and Cheila Rocha are supported by Ph. D. grants from Fundacao para a Ciencia e